2016
DOI: 10.14744/anatoljcardiol.2015.6654
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic nervous dysfunction detected by both heart rate variability and heart rate turbulence in prediabetic patients with isolated impaired fasting glucose

Abstract: Objective:Cardiac autonomic nervous dysfunction (CAND), a severe complication of diabetes, has also been shown to affect prediabetic patients. The role of isolated impaired fasting plasma glucose (IFG), a subtype of prediabetes, is not clear in the pathogenesis of CAND. The aim of this study was to examine the relationship between isolated IFG and cardiac autonomic function using heart rate variability (HRV) and heart rate turbulence (HRT) indices derived from 24-h Holter–electrocardiogram recordings.Methods:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
5
0
1
Order By: Relevance
“…Synchronization of low-frequency oscillations may be useful in cardiac event risk stratification ( 11 ) and control of therapeutic treatment ( 12 ) in patients with hypertension and MI. Further research regarding the interaction between slow oscillations in HRV and PPGV among prediabetic patients may complete and expand the results of Dr. Balcıoğlu et al ( 7 ).…”
supporting
confidence: 51%
See 2 more Smart Citations
“…Synchronization of low-frequency oscillations may be useful in cardiac event risk stratification ( 11 ) and control of therapeutic treatment ( 12 ) in patients with hypertension and MI. Further research regarding the interaction between slow oscillations in HRV and PPGV among prediabetic patients may complete and expand the results of Dr. Balcıoğlu et al ( 7 ).…”
supporting
confidence: 51%
“…Balcıoğlu et al ( 7 ) demonstrated the association between prediabetic condition (isolated fasting hyperglycemia) and CAND in an article in the current issue of the Anatolian Journal of Cardiology entitled “Cardiac autonomic nervous dysfunction detected by both heart rate variability and heart rate turbulence in prediabetic patients with isolated impaired fasting glucose.” HRT abnormality, considered an autonomic imbalance, was found in prediabetic patients. According to Balcıoğlu et al ( 7 ) and some other researchers ( 8 , 9 ), damage to neurofibers responsible for regulating cardiac and vascular function under hyperglycemia is one reason for CAND in diabetic patients. This statement is supported by the association between isolated fasting hyperglycemia and all evaluated parameters of autonomic cardiac regulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It must be emphasized that the current study highlights a certain difference between prediabetic and normal people in ECGs; however, this difference is usually ignored in clinical practice. Among them, Balcıoğlu et al found that IGR patients exhibited different degrees of CAND, by recording the heart rate variability and heart rate turbulence indexes of 24-h dynamic ECGs [ 42 ]. Yu et al adopted dual-source computed tomography to evaluate the relationship between coronary atherosclerosis (CAA) and blood glucose levels; they found that the prevalence of CAA in the prediabetic group was slightly higher than that of the normoglycemic group but lower than that of the diabetic group, which indicates that prediabetic patients have an increased risk of CAA.…”
Section: Resultsmentioning
confidence: 99%
“…En el embarazo producto del estrés metabólico la intolerancia a los carbohidratos también suele ser una afección temporal [4]. En estas patologías existe una alteración de la VFC con un predominio simpático considerado como un signo de alteración en el sistema nervioso autónomo (SNA) [5].…”
Section: Capítulo 1: Introducciónunclassified